2018
DOI: 10.1159/000489053
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast versus Adipocyte: Bone Marrow Microenvironment-Guided Epigenetic Control

Abstract: The commitment and differentiation of bone marrow mesenchymal stem cells (MSCs) is tightly controlled by the local environment ensuring lineage differentiation balance and bone homeostasis. However, pathological conditions linked with osteoporosis have changed the bone marrow microenvironment, shifting MSCs’ fate to favor adipocytes over osteoblasts, and consequently leading to decreased bone mass with marrow fat accumulation. Multiple questions related to the underlying mechanisms remain to be answered. As re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…There is an inverse relationship between osteogenic and adipogenic differentiation. 27 This inverse relationship is indicated by the concurrent upregulation of RUNX-2 (a master regulator of osteogenesis) and downregulation of the adipogenic marker PPAR-γ (which induces cells to differentiate into adipocytes). [28][29][30] In addition, supplementation with a high (300 ng/mL) SeNP concentration results in excessive ROS generation with compromised antioxidant defense and decreased cell viability.…”
mentioning
confidence: 99%
“…There is an inverse relationship between osteogenic and adipogenic differentiation. 27 This inverse relationship is indicated by the concurrent upregulation of RUNX-2 (a master regulator of osteogenesis) and downregulation of the adipogenic marker PPAR-γ (which induces cells to differentiate into adipocytes). [28][29][30] In addition, supplementation with a high (300 ng/mL) SeNP concentration results in excessive ROS generation with compromised antioxidant defense and decreased cell viability.…”
mentioning
confidence: 99%
“…Recent studies have highlighted the importance of epigenetic changes in the lineage determination of adipogenesis and osteogenesis [ 35 , 36 ]. BMSC differentiation towards a lineage fate is associated with activation of lineage-specific gene expression and repression of other cell type-specific genes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the presence of ROS and pro-inflammatory cytokines provides a favorable environment for adipogenesis and fat accumulation, and impairs bone regeneration, thus leading to the development of osteoporosis. 51 …”
Section: Dna Damage Response In Osteogenesismentioning
confidence: 99%